Modification of KSU swine finishing facility hovers, floors, or supplemental heat - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to evaluate the benefits of modifying the KSU swine finishing barn by adding hovers, flooring, or both with and without supplemental heat. In trial 1, pigs with no supplemental heat, hover or floor gained significantly poorer than pigs with supplemental heat plus floor, supplemental heat plus hover and floor, or no heat and floor. Pigs with no heat but with hover, floor or both gained similarly with pigs having the benefit of supplemental heat plus modifications. Average daily gain and feed per lb gain were similar for pigs exposed to supplemental heat and those exposed to no supplemental heat. These data would suggest that finishing pigs (100 lbs plus) can perform satisfactorily without supplemental heat, if a hover or floor is provided. The second trial was conducted during March, April, and May, at which time the average temperature was above 50F, consequently no differences were observed in pig performance due to building modifications.
Keywords: Swine; Swine Finishing Facility; Hovers; Supplemental heat